2013
DOI: 10.1371/journal.pone.0071372
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Susceptibility to Spontaneous Seizures of Noda Epileptic Rats by Loss of Synaptic Zn2+

Abstract: Zinc homeostasis in the brain is associated with the etiology and manifestation of epileptic seizures. Adult Noda epileptic rats (NER, >12-week-old) exhibit spontaneously generalized tonic-clonic convulsion about once a day. To pursue the involvement of synaptic Zn2+ signal in susceptibility to spontaneous seizures, in the present study, the effect of zinc chelators on epileptogenesis was examined using adult NER. Clioquinol (CQ) and TPEN are lipophilic zinc chelotors, transported into the brain and reduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
10
0
2
Order By: Relevance
“…Lavoie et al. reported that intracellular zinc chelators influence more neuronal excitability of the CA3 region of the hippocampus using a high [K + ] model of epilepsy for status epilepticus rather than extracellular zinc chelators.…”
Section: Zinc and Epilepsymentioning
confidence: 99%
“…Lavoie et al. reported that intracellular zinc chelators influence more neuronal excitability of the CA3 region of the hippocampus using a high [K + ] model of epilepsy for status epilepticus rather than extracellular zinc chelators.…”
Section: Zinc and Epilepsymentioning
confidence: 99%
“…(i) Clioquinol (5-chloro-7-iodo-quinolin-8-ol) is a halogenated 8-hydroxyquinoline (14). It was selected because it has been extensively used as a zinc chelator both in vitro and in vivo (15)(16)(17)(18)(19). Clioquinol (Fluca, 33931-100MG-R) was diluted to a 0.05 M stock solution in 100% dimethyl sulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…(vii) N,N,N=,N=-tetrakis(2-pyridylmethyl)ethane-1,2-diamine (TPEN) is a membrane-permeative zinc chelator that has also been used extensively in that role in vivo (18,19,32,33) and on A. fumigatus (25). TPEN (Life Technologies, T1210) was diluted to a 0.05 M stock solution in 100% DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Важливим аспектом фармакотерапії нейродегенеративних, цереброваскулярних та інших за-хворюваньЦНС,ветіологіїякихзначнурольвідіграютьстресіпорушенняметалолігандногогомео-стазуєнейропротекція,якарозглядаєтьсяякзахистнейронівприсудиннійпатологіїголовногомоз-ку.Однакнасьогоднівеликакількістьпроведенихклінічнихдослідженьстраждаютьнавідсутність задовільнихдоказівефективностідіїхелаторів,дляцьоготакожнеобхіднодослідитифізіологічні механізмиметалолігандногогомеостазу (Кудрин,Громова,2006;Zalups&Koropatnick,2010;Takeda et al, 2013).…”
Section: метаболізмметалівугіпокампітарольцинкувпатогенезіепілептифорunclassified
“…Добревідомо,щонадлишковезвільненняцинкупідчаснейрональноїактивностіможепризво-дитидопорушеньзбудливостігіпокампу,утомучислівиникненнюсудомноїактивності (Elsas et al, 2009;Takeda et al,2013;Kazemi et al, 2016).…”
Section: результати та їх обговоренняunclassified